2-Hydeocy 4-n-Butoxy Butyrophenone Oxime as an Analytical Regent for Nickel. - Talati, J.D.; Parikh, K.S. (Asian Journal of Chemistry, 2010)
In the present work, the authors describe 2-hydroxy, 4-n-butoxy butyrophenone oxime gravimetric and photometric reagent for nickel.